2019
DOI: 10.1103/physrevb.99.184422
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the formation of nanoprecipitates with magnetically disordered regions in bulk Ni50Mn45In5 Heusler alloys

Abstract: Shell ferromagnetism is a new functional property of certain Heusler alloys which was recently observed in Ni 50 Mn 45 In 5 . We report the results of a comparative study of the magnetic microstructure of bulk Ni 50 Mn 45 In 5 Heusler alloys using magnetometry, synchrotron x-ray diffraction, and magnetic small-angle neutron scattering (SANS). By combining unpolarized and spin-polarized SANS (so-called POLARIS) we demonstrate that a number of important conclusions regarding the mesoscopic spin structure can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The lattice parameters of the 14M structure vary as a function of indium content and heat treatment. For the AQ-In10, the lattice parameters are lower than those of the Ni 50 Mn 40 In 10 bulk alloy [5], while the lattice parameters of the L1 0 are different from those reported for the Ni 50 Mn 45 In 5 alloys [5,27]. The discrepancies between the present results and those reported earlier might be ascribed to the experimental conditions, such as the preparation method, alloy composition, and heat treatments (time and temperature), that can influence the structure, phase transformation, structural defects, lattice parameters, crystallite sizes, etc.…”
Section: Structurementioning
confidence: 57%
“…The lattice parameters of the 14M structure vary as a function of indium content and heat treatment. For the AQ-In10, the lattice parameters are lower than those of the Ni 50 Mn 40 In 10 bulk alloy [5], while the lattice parameters of the L1 0 are different from those reported for the Ni 50 Mn 45 In 5 alloys [5,27]. The discrepancies between the present results and those reported earlier might be ascribed to the experimental conditions, such as the preparation method, alloy composition, and heat treatments (time and temperature), that can influence the structure, phase transformation, structural defects, lattice parameters, crystallite sizes, etc.…”
Section: Structurementioning
confidence: 57%
“…They observed fewer and larger clusters when higher temperature and longer time ageing processes were used. They also determined that the martensitic phase decomposition is a process characterized by a two-step linear kinetic regime: the first one with a larger slope was observed for aging times below 16 h, and the second one with a smaller slope for aging times larger than 16 h. The presence of ferromagnetic nanoprecipitates in an antiferromagnetic matrix was reported by Benacchio et al [78] in a bulk Ni 50 Mn 45 In 5 MetaMSMA field-annealed at 700 K. The results were obtained by combining unpolarized and spin-polarized SANS. This phenomenon was also studied by Sarkar et al [79], who demonstrated the presence of spin-clusters of structural origin in a Ni 45 Co 5 Mn 38 Sn 12 MetaMSMA, which are related to the martensitic transformation.…”
Section: Large Scale Structures 221 Small-angle Neutron Scattering (Sans)mentioning
confidence: 60%
“…The moment in such systems is strongly confined to Fe and Mn, with the FM or AFM arising from a subtle balance between Sn-mediated AFM superexchange and the itinerant electron FM RKKY (Ruderman-Kittel-Kasuya-Yoshida) interaction [20]. These calculations also highlighted a tendency to chemical phase separation [20], no doubt frustrated by quenching, as in other Heusler-based systems [22][23][24]. A tendency to form (111)-oriented stripes and short-range-ordered clusters of Fe-and Mn-rich FM and AFM phases was uncovered [20].…”
Section: Introductionmentioning
confidence: 85%